Microstructure evolution of the A380 aluminum alloy semi-solid slurry prepared by serpentine channel - LIU Zhi-yong; MAO Wei-min; WANG Wei-fan; ZHENG Zhi-kai (工程科学学报)
The semi-solid slurry of A380 aluminum alloy was prepared by using a graphite serpentine channel and the microstructure evolution during solidification was investigated. The result showed that, initial solidification occurred in the serpentine channel, and a large number of primary free grains generated in the alloy melt under the influence of chilling and heterogeneous nucleation caused by the serpentine channel inner wall. Secondary non-dendrites formed during secondary solidification which occurred in the remaining alloy melt of the semi-solid slurry in the collective crucible. The drifting model of primary grains displayed that a part of primary free grains directly grew to spherical grains, and others developed to dendrites. The "self-stirring" of the alloy melt made dendrites neck and fuse, and they got initial spheroidization and ripening through the " self-rotating" in the serpentine channel. Secondary non-dendrites formed during secondary solidification got initial spheroidization and ripening in the collective crucible. Mean-while, the primary grains got further spheroidization, ripening and uniform distribution in the collective crucible.